(Derivatives in douaa Alahad: a semantic morphologicalstudy) - misanjas, misanjas; shehab Ahmed, Zahraa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
This studdy dealt with (derivatives in douaa Alahad: a semantic morphologicalstudy) atopic that occupieslarge space in the Arabic language, especially the science of morphology, which is concerned with the structure of the Arabic word in terms of construction and declension, and the changes that occur to it, such as substitution, causative, derivation, and others. We focused on an important topic, which is the derivation, and tried to stand on several issues, the most important of which is highlighting the significant role that the research topic occupies. It is an attempt to provide a glimpse of it in the midst of studies about it and the identification of an important aspect of the Arabic language, which is the topic of derivatives, and their types, forms and how they are derived, through exposure to an important douaa from our immortal heritage, which is douaa Alahad. This topic is of clear importance in languages in general and Arabic in particular, as it constitutes a basic support in the linguistic research on the origins of words and their impact on sentences.